Faktor yang Memengaruhi Penggunaan Sistem Informasi Rumah Sakit Berdasarkan Metode Technology Acceptance Model di RSU Advent Kota Medan - Arifah Fitriani; Adistia Maulidiah (Akademi Perekam dan Informasi Kesehatan Imelda, 2022)
Until now, there is no guarantee that every hospital is able to implement a Hospital Information System (SIRS) properly. Medan Adventist General Hospital has organized SIRS since 2018, but its use is still not optimal. This study aims to determine the factors that influence the use of SIRS with a technology acceptance model approach. The data used is primary data. The total respondents obtained in this study were 197 and the statistical tests used were chi-square and structural equation modeling.. The regression weight test showed that perceived usefulness was only significantly influenced by length of work experience (e = 0.173), and computer facilitation (e = 2.235). Meanwhile, perceived ease of use was only significantly influenced by length of work experience (e = -0.223), ability to operate computers (e = 0.439) and computer facilitation (e = 4.842).